Zuwanderung nach Deutschland - Problem und Chance für den Arbeitsmarkt - Christina Gathmann; Nicolas Keller; Ole Monscheuer; Thomas Straubhaar; Holger Schäfer; Klaus F. Zimmermann; Herbert Brücker (Wirtschaftsdienst, 2014)
Seit 2008 kamen - vor allem aus der Europäischen Union - zunehmend mehr Einwanderer nach Deutschland als wegzogen. Motiviert waren diese nicht wie befürchtet durch die großzügigen Sozialleistungen, sondern durch die Aussicht auf Arbeit. Gleichzeitig mit der Struktur der Herkunftsländer hat sich auch die Qualifikation der Zuwanderer verbessert, was sich angesichts des prognostizierten Fachkräftemangels positiv auf den Arbeitsmarkt auswirkt. – – The size and composition of the most recent wave of immigrants to Germany and the potential effects of immigration on employment and the wages of native workers are the focus of the above articles. The authors agree that Germany needs immigration. But the benefit for locals depends on the migrants' human capital endowment. Most of these immigrants are EU citizens. Thus, the existence of a sizeable amount of low-skilled immigration cannot be prevented. A major challenge is going to be to alleviate unwanted effects by integrating low-skilled immigrants into the labour market and finding adequate jobs for the high-skilled. A flexible labour market is the most important prerequisite for continued labour market success of immigrants in Germany. Labour migration contributes necessary flexibility to the German economy aids, its global integration and provides needed human resources. The single EU labour market has to be complemented by labour mobility partnerships with other countries.
Keywords: J11; J21; J61; 330; Einwanderung; Freizügigkeit; Beschäftigungseffekt; Arbeitskräftepotenzial; Arbeitsmarkt; Deutschland